13th Annual Congress of the European College of Sport Science - ECSS 2008 - Estoril 09.-12.7.2008 - Sport science by the sea (13th Annual Congress of the European College of Sport Science - ECSS 2008 - Estoril 09.-12.7.2008, 2008)
The 13th Annual Congress of the ECSS of the ECSS aims to provide an international forum for the presentation and discussion of the latest research in sports science and its related fields The panel of distinguished scholars who are invited to share their expertise with the members of the scientific and professional community will, without any doubt, prove invaluable to its success. The Scientific Programme is composed of more than 1.700 abstracts, which were accepted after being carefully reviewed. This year's Congress is the largest in the history of the ECSS, underlining both the interest of the sport scientific community and the importance of the ECSS as an interdisciplinary forum for ongoing debate. In view of the multifaceted character of sport science, state-of-the-art presentations cover basic and applied sciences as they relate to sport, exercise and health. The presented abstracts comprise not only all relevant sub-disciplines of sport science but also all continents and 68 different nations. The abstracts are distributed among 4 Plenary Sessions, 37 Invited Symposia, 74 Thematic Sessions and 3 Poster Sessions, each presenting close to 400 Posters.